Kepatuhan Syariah pada Hybrid Contracts dalam IMBT: Studi Analisis Fiqh dan Regulasi Modern - Anwar, Desy Rahmawati; Haeriyah, H.Hamzah; Kara , H. Muslimin H. (CV. Lenggogeni Data Publishing, 2025)
Hybrid contracts, as implemented in Ijarah Muntahiya bi al-Tamlik (IMBT), represent a significant innovation in Islamic finance. This article aims to analyze the Sharia compliance of hybrid contracts within IMBT through the perspectives of fiqh and modern regulations. Utilizing a qualitative approach that integrates literature review, fiqh analysis, and related regulations, the study finds that IMBT effectively combines ijarah and sale/hibah contracts. However, its implementation often faces challenges such as a lack of transparency and the potential for gharar. This study recommends strengthening regulations and enhancing Sharia supervision to ensure practices align with Islamic principles. The research provides theoretical and practical contributions to developing more inclusive and sustainable Islamic finance.